The Medical Malpractice Transformation in the Internet of Medical Things Era - Payasan, Lalu Guntur; Runturambi, Arthur Josias S.; Sulhin, Iqrak (Technium Social Sciences Journal, 2022)
The Internet of medical things brought changes to the practice of medicine. The change is due to the inclusion of elements of devices and networks in medical services. The device and network elements in medical devices have many vulnerabilities that can lead to losses experienced by patients when they receive medical services. Therefore, this study will examine how these changes then have an impact on losses that in criminology are considered medical malpractice. A qualitative explanatory approach to both primary and secondary data is then used by researchers to support the argumentation. The results showed that the argument for the possibility of other perpetrators besides doctors who could then be interpreted as committing crimes that cause harm to patients was proven to be good from the responsibility of other human beings (electromedicine) as guarantors of device safety and reliability; manufacture and distributor of devices both from the prototype process, to use in health care facilities; and providers and hackers in the network used by healthcare devices. The impact can be seen in the discussion